Prace dyplomowe napisane pod kierunkiem o. prof. dr. hab. Bazylego Degórskiego OSPPE - Dzhana, Olha (Vox Patrum, 2025)
A list of the diploma theses written under the supervision of Fr. Prof. dr. hab. Bazyli Degórski OSPPE